TORAKOCHIRURGIASurgical considerations in the therapy of pleural empyema - Jabłoński, Sławomir; Wawrzycki, Marcin; Stolarek, Robert A.; Figlus, Małgorzata; Jabłonowski, Zbigniew; Santorek-Strumiłło, Edyta; Piskorz, Łukasz; Kordiak, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: The therapy of pleural empyema is the most challenging issue in surgery due to long-term hospitalization, high costs and frequent complications as well as the high mortality rate exceeding 20%. Aims: The study aimed to evaluate early results of pleural empyema therapy with respect to therapeutic modality, pleural empyema phase, aetiology, image study patterns, general patient state and coexisting diseases. Material and Methods: The study involved the retrospective review of 51 patient medical records with the diagnosis of pleural empyema within two years. Results: The study enrolled 42 male and 9 female patients. The serous, fibropurulent and organization stage of pleural empyema were 19.6%, 70.6% and 9.8%, respectively. With regard to aetiology, the majority were parapneumonic empyemas 66.7%, then iatrogenic 12.7%, post-traumatic 9.8%, and the remaining 2%. The bacterial cultures produced positive results in 32 patients. The most common were aerobic pathogens: Klebsiella pneumoniae (12.5%), Staphylococcus aureus (9.4%) and Pseudomonas aeruginosa in addition to anaerobic Bacteroides fragilis (6.2%). In 9 patients (28.1%) mixed bacterial pathogens were found. The majority of patients were in a poor general state and their immune system was impaired due to the underlying condition. Conclusions: The therapy of pleural empyema requires a differential approach with regard to: general state of patient, dimensions and empyema location, disease duration, coexisting lung pathology and surgical experience. Superior results are achieved with early stages of pleural empyema using antibiotic therapy, pleural drainage along or with the administration of fibrinolytics or videothoracoscopy. Empyemas in the late, fibropurulent or organization stage usually require thoracotomy with decortication. Serious general condition, coexisting conditions and surgical complications are associated with a high percentage of fatal final outcomes.